Job enrichment on key performance indicators (KPI) as a measurement of increasing staff competency and performance appraisal - Wido Untoro; Miftahul Jannah S; Budi Sampurno (International Journal of Applied Finance and Business Studies, 2023)
Manufacturing companies that produce tobacco-based products not only face regulatory and marketing obstacles, but also intense competition between competitors. Companies can survive and develop their business, if they are supported by competent employees with high work performance. This research aims to measure performance assessment using an employee competency approach using key performance indicators (KPI) which are used as job enrichment instruments, as well as finding a competency development model through job enrichment treatment. The research took a sample of employees at PT. ITIC, tbk at staff level from all areas of work in the company. Data was collected through work performance assessment documents and questionnaires, which were then analyzed using time series regression.